Ionically Self-Assembled, Multi-Luminophore One-Dimensional Micro- and Nanoscale Aggregates of Thiacarbocyanine GUMBOS - de Rooy, Sergio L. (2012)
Groups of uniform materials based on organic salts (GUMBOS), derived from thiacarbocyanine (TC)-based dyes with increasing methyne chain lengths, were prepared through a single-step metathesis reaction between the iodide form of the TC dye and lithium bis(perfluoroethylsulfonyl)imide as the lipophilic anion source. Ionic self-assembly of these fluorescent hydrophobic GUMBOS resulted in aqueous dispersions of one-dimensional micro-and nano-scale molecular aggregates. Blended binary and ternary aggregates containing multiple TC GUMBOS were also prepared. These nanostructures exhibited a variety of aspect ratios, affording tunable Förster resonance energy transfer (FRET) and aggregation-dependent spectroscopic properties.